Gender Differences in Academic Productivity within Pediatric Dentistry Departments in Turkey - Kiziltan Eliacik, Basak; Karahan, Meltem (UI Scholars Hub, 2021)
Objective: To investigate the differences in the academic productivity of male and female academicians from the departments of pediatric dentistry in the Faculties of Dentistry in Turkey. Methods: A search was made of international studies indexed in PubMed published up until January 2021 by a total of 241 academicians in the Departments of Pediatric Dentistry of 79 Faculties of Dentistry in Turkey. The total number of international publications for each faculty member was obtained from the institutional websites and thorough searches of PubMed and Web of Science. H-index and the number of citations were established through an advanced search of the Web of Science. Results: The study included 241 faculty members, consisting of 62 (25.7%) males and 179 (74.3%) females, from 79 faculties of dentistry. Male academicians had a statistically significantly larger number of citations from their publications indexed in PubMed than their female counterparts (p = 0.003). An examination of the h-index values from the Web of Science database revealed that male faculty members had significantly higher h-indices than female faculty members (p = 0.005). Conclusions: Although a majority of academicians in pediatric dentistry are female, large differences exist between female and male faculty members in citations and h-indices.